THE DYNAMIC CONCEPT OF WELFARE STATE IN INDONESIAN CONSTITUTION - Mohammad Tavip (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThis paper analyzes the dynamics of welfare state concepts in Indonesia in accordance with the Indonesian Constitution (UUD 1945) through legalization spectrums and social policies in three regime orders, namely: old order, new order and reformation order. The welfare state concept is one enabling the government to measurably act as a social welfare accelerator. The legal reviewtowards this concept is further elaborated in such a way that it touches the dimensions of ideology, democracy and politics. These dimensions advocatesabout the shadows of inevitable effects of two world ideology mainstreams to thelegal realities and social policies in Indonesia as a welfare state based on itsState Ideology (Pancasila). With reference to the aforementioned facets of analysis, it is definitely implied that there were strong impacts from both technical and legal predicaments during the transition phase in the early independence of Republic of Indonesia and changes in constitutional structure in Indonesia post reformation to the dynamics of concepts of welfare state in Indonesia. Accordingly, this paper addresses the concept dynamics in terms of constitutional precisions in the line with welfare state of Indonesia.Keywords: Indonesian Welfare State Concept, State Ideology (Pancasila), Third-Way Ideology from minimal model to minimal-plural model.